ANALYSIS OF THE RATIONAL RELATIONS TO THE COMPANY’S WORK METTERS (CASE STUDY ON PT. Semen Gresik (Persero), Tbk) - Ulfah, Almira Keumala; Ramadhan, Ramadhan; Bungkes, Panetir; Ismail, Sherif Mohamed (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
This study presents a comprehensive analysis of the rational relations pertaining to the operational dynamics of PT. Semen Gresik (Persero), Tbk, a leading cement manufacturing company. Through a detailed case study approach, various facets of the company's operational framework are scrutinized, focusing on key financial metrics such as liquidity, leverage, and profitability. By examining these rational relations, the study aims to elucidate the company's ability to effectively manage its resources, meet short-term obligations, and sustain profitability amidst dynamic market conditions. Employing a range of financial ratios including liquidity ratio, leverage ratio, and net profit margin, the analysis provides insights into PT. Semen Gresik (Persero), Tbk's financial performance over a specified period. The study delves into the implications of these findings on the company's operational efficiency and financial stability, highlighting areas of strength and opportunities for improvement. By deciphering the rational relations inherent in the company's operational matters, this study offers strategic recommendations to optimize performance and enhance competitiveness in the industry landscape. Through a rigorous examination of rational relations, this study contributes to a deeper understanding of PT. Semen Gresik (Persero), Tbk's operational dynamics and its implications for organizational success. By elucidating the intricate connections between financial metrics and operational outcomes, the study provides valuable insights for stakeholders, policymakers, and industry practitioners seeking to navigate the complexities of contemporary business environments and drive sustainable growth and profitability